2019
DOI: 10.1039/c9cc06956a
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric and electrocatalytic production of hydrogen peroxide driven by a water-soluble copper(ii) complex

Abstract: Herein, a water-soluble molecular copper complex was investigated as a catalyst for O2 reduction in both water and an organic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Mononuclear Cu complexes have been explored to catalyze the ORR. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Additionally, several dinuclear complexes have been investigated to induce a cooperative effect during ORR catalysis. [35][36][37][38] We have recently shown that the mononuclear complex [Cu(tmpa)(solv)] + (Cu-tmpa, tmpa = tris(2-picolyl) amine) shows exceptionally high ORR catalytic performance with a turn-over frequency (TOF) of almost 2 million per second.…”
Section: Introductionmentioning
confidence: 99%
“…Mononuclear Cu complexes have been explored to catalyze the ORR. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Additionally, several dinuclear complexes have been investigated to induce a cooperative effect during ORR catalysis. [35][36][37][38] We have recently shown that the mononuclear complex [Cu(tmpa)(solv)] + (Cu-tmpa, tmpa = tris(2-picolyl) amine) shows exceptionally high ORR catalytic performance with a turn-over frequency (TOF) of almost 2 million per second.…”
Section: Introductionmentioning
confidence: 99%
“…The manganese(II) complex bearing N , N ‐bis(2‐picolyl)amine backbone with a pendant ethanol side chain (HN 3 O; 2‐(bis[pyridin‐2‐ylmethyl]amino)ethanol), [Mn(HN 3 O)(CH 3 CN)(ClO 4 )](ClO 4 ) ( 1 ), and [Mn(HN 3 O)]Cl 2 were synthesized according to the modified literature methods 38,39 …”
Section: Resultsmentioning
confidence: 99%
“…A white Mn( ii ) complex was prepared by following a modified literature procedure (details can be found in the ESI†). 9 The electrospray ionization mass spectrometry (ESI MS) spectrum exhibited a prominent peak at m / z of 441.1, whose mass and isotopic distribution patterns corresponded to a monomeric Mn complex, [Mn(HN 3 O 2 )(ClO 4 )] + (calculated m / z of 441.1) (Fig. S1a, ESI†).…”
mentioning
confidence: 99%